Community Interpreting: signed or spoken? Types, modes, and methods - Grbić, Nadja; Pöllabauer, Sonja (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article focuses on the similarities and differences between spoken and signed language Community Interpreting (CI). After a briefoverview of the various terms that are generally used in the relevant literature – albeit in- consistently – to categorize various sorts of interpreting (type, mode, setting), we examine a number of typologies of interpreting events that have been developed in order to allowfor a more complex categorization of such events. A briefoutline of the history of research into spoken and signed language CI is complemented by a short description of the similarities and differences between spoken and signed language CI. We also discuss various examples of research methods that have been applied to spoken and signed language CI.